2017
DOI: 10.3390/nu9040318
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Breakfast Rich in Slowly Digestible Starch on Glucose Metabolism: A Statistical Meta-Analysis of Randomized Controlled Trials

Abstract: Starch digestibility may have an effect on the postprandial blood glucose profile. The aim of this meta-analysis was to analyze the relationship between Slowly Digestible Starch (SDS) levels and plasma glucose appearance and disappearance rates, as well as other parameters of glucose metabolism, after healthy subjects consumed cereal products that differed in SDS content. Three randomized controlled clinical trials that included a total of 79 subjects were identified. Using binary classification for the variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 45 publications
1
22
0
1
Order By: Relevance
“…19-22% of E) and similar levels of other macroelements. 35 MacNeil et al obtained similar results by assessing the effect of an increased supply of dietary fiber on glucose and insulin levels after breakfast in a group of 12 diabetic patients. 36 In this study, it was observed that replacing 20 g of simple carbohydrates with complex carbohydrates in a breakfast bagel (total carbohydrate content 50 g) significantly reduced glucose and insulin blood levels after the meal compared to the results after eating a product with the same total carbohydrate content but lower dietary fiber content (2 g).…”
Section: The Relationship Between Consumption Of High-fiber Products mentioning
confidence: 72%
“…19-22% of E) and similar levels of other macroelements. 35 MacNeil et al obtained similar results by assessing the effect of an increased supply of dietary fiber on glucose and insulin levels after breakfast in a group of 12 diabetic patients. 36 In this study, it was observed that replacing 20 g of simple carbohydrates with complex carbohydrates in a breakfast bagel (total carbohydrate content 50 g) significantly reduced glucose and insulin blood levels after the meal compared to the results after eating a product with the same total carbohydrate content but lower dietary fiber content (2 g).…”
Section: The Relationship Between Consumption Of High-fiber Products mentioning
confidence: 72%
“…First, a high SDS content is a key factor for decreasing the rate of appearance of exogenous glucose (RaE) in the blood stream, and thus for reducing the glycemic and insulinemic responses in healthy adults. This study showed a 15-fold greater chance of having a low RaE and a 5-fold greater chance of having a low glycemic response after consuming a high-SDS food product compared to a low-SDS food product [35]. In addition, a reduction in the RaE was associated with a significant reduction in the postprandial glycemic and insulinemic responses [36].…”
Section: Discussionmentioning
confidence: 61%
“…These studies provide insights on the SDC benefits and its underlying mechanisms. In a clinical study [27], breakfast with high-SDC and low GI containing cereal products consumed for five weeks reduced appearance of glucose in the early part of the morning and extended the glucose release into the later part of the morning. The strength of the current study is a preliminary understanding of glycemic index and the steady glucose release effects of starch-based SDC alone and in food form of broader consumer relevance.…”
Section: Discussionmentioning
confidence: 99%